2009
DOI: 10.1097/sla.0b013e3181b0fc8b
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Gemcitabine Plus S-1 Chemotherapy Improves Survival After Aggressive Surgical Resection for Advanced Biliary Carcinoma

Abstract: Adjuvant gemcitabine plus S-1 chemotherapy may be one of several factors contributing to improved outcomes after aggressive surgical resection of advanced biliary carcinoma in recent years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
97
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 51 publications
4
97
2
1
Order By: Relevance
“…In pancrea to duodenectomy for pancreatic cancer, the CONKO-001 and JSAP-02 trials revealed that dose modification was frequently necessary for completion [15,16]. In BTC, Murakami et al presented gemcitabine-based adjuvant chemotherapy, however, all patients could not complete the protocol, even for biweekly 700 mg/m 2 gemcitabinebased chemotherapy [14]. Clinically, several omittances are necessary in the usual 4-weekly protocol of gemcitabine after BTC surgery, and it become like the 3-weekly protocol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pancrea to duodenectomy for pancreatic cancer, the CONKO-001 and JSAP-02 trials revealed that dose modification was frequently necessary for completion [15,16]. In BTC, Murakami et al presented gemcitabine-based adjuvant chemotherapy, however, all patients could not complete the protocol, even for biweekly 700 mg/m 2 gemcitabinebased chemotherapy [14]. Clinically, several omittances are necessary in the usual 4-weekly protocol of gemcitabine after BTC surgery, and it become like the 3-weekly protocol.…”
Section: Discussionmentioning
confidence: 99%
“…And, there have been several reports of gemcitabine-based adjuvant chemo therapy following major hepatic to mine for BTC or pancrea to duodenectomy for pancreatic cancer, which have suggested that dose modification is often necessary or that the usual 4-weekly protocol could not be, or was not applied [14][15][16]. Because of the morbidity, liver dysfunction, and low performance status (PS) after BTC surgery (major hepatectomy/pancreatoduodenectomy), it would seem difficult to complete the usual 4-weekly protocol, and frequent pauses during the adjuvant during therapy would be necessary.…”
Section: Comparison Of 4-weekly Vs 3-weekly Gemcitabine As Adjuvant Cmentioning
confidence: 99%
“…Takada et al demonstrated that patients with GBC receiving adjuvant therapy consisting of mitomycin C and 5-FU after surgery had an improved overall survival (22). Some have recommended adjuvant chemotherapy and chemoradiotherapy after surgery for biliary carcinoma, as shown in Table III (21,24,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). However, the results of adjuvant external-beam radiation therapy with concurrent 5-FU treatment were unsatisfactory, with a 5-year survival rate of less than 40% (38)(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of periampullary carcinoma, only one randomized control trial has demonstrated the efficacy of the combination adjuvant therapy of mitomycin C and 5-FU for GBC (22). Most recently, a retrospective study on adjuvant therapy with gemcitabine plus S-1 chemotherapy after aggressive surgery significantly improved prognosis, with 57% survival at 5 years after surgery (23,24).…”
mentioning
confidence: 99%
“…Previously, the combination of GEM and 5-FU was shown to have a marked synergistic cytotoxic effect against pancreatic cancer cells (25). In addition, recent increasing evidence suggests that GEM and S-1 combination offers promising survival benefit with acceptable toxicity in patients with advanced biliary tract cancer (26,27) and nonsmall cell lung cancer (28,29) as well as advanced pancreatic cancer (10)(11)(12). Furthermore, GEM and S-1 have an indication for the treatment of pancreatic cancers regardless of pathogical types in Japan.…”
Section: Discussionmentioning
confidence: 99%